VALIDITY AND PRACTICALITY OF WORDWALL AS LEARNING MEDIA ON CREATURE INTERACTION MATERIAL CLASS VII - Siti Sundusiatul Firdausiyah; Noer Af'idah (Program Studi Pendidikan IPA FIP Universitas Hasyim Asy'ari, 2025)
The purpose of this study was to develop valid and practical wordwall learning media to be useful for reinforcement on the material of the interaction of living things and their environment class VII at MTs Jombang. The development model used in this research is the ADDIE model which has stages, namely: Analyse, Design, Development, Implementation, and Evaluation. The validity test was carried out with media assessment by material expert validators, media experts and science teachers. The practicality test was carried out by filling out a student response questionnaire about the attractiveness of wordwall learning media. The results of the validity test and the practicality test of wordwall media get an average score of 3.4 with valid criteria and 96.3% with very practical criteria. Based on these data, the development of wordwall learning media is valid and practical for use in the learning process in strengthening the material on the interaction of living things and their environment in class VII.